The traditional cultural landscape of Pico Island and its vernacular architecture, Portugal - Carlos, Gilberto Duarte (2022)
In the middle of the Atlantic Ocean is located the Azores archipelago, composed by nine volcanic islands. Pico island was the seventh to be discovered by Portuguese sailors, during the 15th century. Its name is due to the pyramidal form of its mountain, a geological volcano reaching 2.351 meters, the highest mountain in Portuguese territory (Costa, 1997). Pico island has an amazing vineyard culture, especially in its western coastline. The exceptional landscape character granted to Pico a World Heritage status in 2004.